Market integration of conventional and organic wheat in Germany - Nadine Würriehausen; Sebastian Lakner; Rico Ihle (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2012)
This paper ... is concerned with interdependencies between organic and conventional wheat prices at the producer level. The analysis is carried out by means of cointegration analysis, that is, the estimation of a vector error correction model considering the two price series. With such a model, empirical evidence on the integration of both markets and the speed of transmission of price signals between them can be obtained. With respect to the transformation in the organic and conventional sector, we want to check, if we find evidences for a structural changes. We assume that an increasing share of supermarkets and discounters in the organic sector play a considerable role and lead to a closer link between organic and conventional prices. First, we present the development of the organic market before we give a description of some theory of price transmission analysis. Then we present the data, the model and estimation results. Finally, we draw conclusions.
Keywords: 330; Weizenmarkt; Ökologischer Landbau; Marktintegration; Deutschland